Pengaruh Transparansi dan Akuntabilitas Pengelolaan Keuangan Desa terhadap Tingkat Kepercayaan Masyarakat pada Pemerintah Desa: Studi kasus: Desa Payu Kecamatan Mootilango Kabupaten Gorontalo - Hawaria Djafar; Rio Monoarfa; Husain, Siti Pratiwi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to determine the effect of transparency and accountability of village financial management has a partial and simultaneous effect on the level of community trust in village government in Payu Village, Mootilango District, Gorontalo Regency. This study uses Quantitative Methods, the data used is primary data obtained from the distribution of questionnaires to the community in Payu Village, Mootilango District, Gorontalo Regency. The sampling technique in this study used the calculation of the solvin formula with a sampling technique using purposive sampling of 86 respondents. The data analysis technique uses multiple linear regression. The results showed that Transparency and Accountability of Village Financial Management on the Level of Community Trust in village government in Payu Village, Mootilango District, Gorontalo Regency. The amount of influence of Transparency and Accountability on the Level of Community Trust in Village Government is 40.6% while the remaining 59.4% is influenced by variables that are not studied